Patient-reported outcome (PRO) measurements in chronic and malignant diseases: ten years’ experience with PRO-algorithm-based patient-clinician interaction (telePRO) in AmbuFlex - Hjollund, Niels Henrik I.; Larsen, Louise Pape; de Thurah, Annette Ladefoged; Grove, Birgith Engelst; Skuladottir, Halla; Linnet, Hanne; Friis, Rasmus Blechingberg; Johnsen, Søren Paaske; May, Ole; Jensen, Annesofie Lunde; Hansen, Troels Krarup; Taarnhøj, Gry Assam; et al. (Quality of life research, 2023)
Background Patient-reported Outcome (PRO) measures may be used as the basis for out-patient follow-up instead of fixed appointments. The patients attend follow-up from home by filling in questionnaires developed for that specific aim and patient group (telePRO). The questionnaires are handled in real time by a specific algorithm, which assigns an outcome color reflecting clinical need. The specific questionnaires and algorithms (named solutions) are constructed in a consensus process with clinicians. We aimed to describe AmbuFlex’ telePRO solutions and the algorithm outcomes and variation between patient groups, and to discuss possible applications and challenges. Methods TelePRO solutions with more than 100 processed questionnaires were included in the analysis. Data were retrieved together with data from national registers. Characteristics of patients, questionnaires and outcomes were tabulated for each solution. Graphs were constructed depicting the overall and within-patient distribution of algorithm outcomes for each solution. Results From 2011 to 2021, 29 specific telePRO solutions were implemented within 24 different ICD-10 groups. A total of 42,015 patients were referred and answered 171,268 questionnaires. An existing applicable instrument with cut-off values was available for four solutions, whereas items were selected or developed ad hoc for the other solutions. Mean age ranged from 10.7 (Pain in children) to 73.3 years (chronic kidney disease). Mortality among referred patients varied between 0 (obesity, asthma, endometriosis and pain in children) and 528 per 1000 patient years (Lung cancer). There was substantial variation in algorithm outcome across patient groups while different solutions within the same patient group varied little. Discussion TelePRO can be applied in diseases where PRO can reflect clinical status and needs. Questionnaires and algorithms should be adapted for the specific patient groups and clinical aims. When PRO is used as replacement for clinical contact, special carefulness should be observed with respect to patient safety.